Evaluation of the effect of the indoor environment on the physiological responses of early-gestation sows in a commercial house in China - Li, Yangyang; Li, Tong; Shang, Bin; Zhao, Yang; Tao, Xiuping; Peng, Feng; Zou, Xiaojun; Zhang, Sixin (Frontiers in Veterinary Science, 2023)
Sows are often influenced by the indoor environment. The objective of this study was to evaluate indoor environmental parameters and physiological responses of early-gestation sows and investigate the possible methods for assessing the thermal environment in commercial house. A total of five early-gestation sows (commercial purebred Yorkshire) with an averaged body weight of 193.20±3.62 kg were used for this study in winter, spring, summer, and autumn. The indoor environment parameters compromising dry-bulb temperature (Tdb), relative humidity (RH), and carbon dioxide (CO2) were recorded in 30-min intervals. Physiological parameters including heart rate (HR) and respiration rate (RR) of sows were also measured every 30 minutes. Wet-bulb temperature (Twb) was calculated using Tdb, RH, and atmospheric pressure recorded at a nearby weather station. The average indoor Tdb and RH were 12.98±2.03°C and 80.4±6.4% in winter, 18.98±2.68°C and 74.4±9.0% in spring, 27.49±2.05°C and 90.6±6.4% in summer, and 17.10±2.72°C and 64.5±10.9% in autumn. A higher average concentration of CO2 was observed in winter (1493±578 mg/m3) than that in spring (1299±489 mg/m3), autumn (1269±229 mg/m3), and summer (702±128 mg/m3). Compared to the HR and RR in the optimum environment, high RH in the house led to a significant decrease in both HR and RR (P<0.05). In addition, a significant decline in HR was also obtained at high temperatures (P<0.05). A temperature humidity index (THI), THI=0.82×Tdb+0.18×Twb, was determined for early-gestation sows, and the THI thresholds were 25.6 for HR. The variation in THI in summer showed that heat stress still occurred under the pad-fan cooling system. This study demonstrated the critical significance of considering physiological responses of early-gestation sows in commercial houses and THI thresholds. We recommend that much more cooling measures should be taken for early-gestation sows in summer.